Affairs of the heart - Sidaway, Ashley; Sidaway, Robert; Sellar, Maurice; Mills, John, Sir (Herts : Screen Entertainment, 1991)
Affairs of the hearts presents eternal struggle between man and women which has been a source of continual fascination for film-maker. British films have accurately potrayed all of these emotions and this programme is a reminder of some of these moving moments. Home, sweet home portraits the foundation of society has always been family life. This programme shows how British film makers have reflected the home with its turbulent emotions, close relationships, calamities and celebrations inboth comical and dramatic fashion.
Home, sweet home
Narrated by John Mills
Keywords: Emotions -- Drama; Family in motion pictures; Motion pictures -- United Kingdom -- History